2015
DOI: 10.1002/mrd.22532
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of androgen receptor in the mouse uterus during early pregnancy and decidualization

Abstract: The androgen receptor (AR) is a ligand-activated transcription factor that is important for both the male and female reproductive systems. The expression and regulation of AR in the uterine endometrium during early pregnancy and decidualization remain relatively under-investigated, so we sought to immunohistochemically examine the spatiotemporal expression of AR in mouse uteri during the peri-implantation period as well as in response to specific steroid hormones. AR protein was found in the nuclei of uterine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Also, androgen‐induced signaling cascades may have a role in stromal decidualization by regulating matrix metalloproteinases, prolactin, and insulin‐like growth factor‐binding protein 1 (Cloke & Christian, ; Cousins et al, ; Gibson, Simitsidellis, Cousins, Critchley, & Saunders, ; Ishikawa, Harada, Kubota, & Aso, ; Kajihara et al, ). In vivo studies in mice and rats as well as in vitro studies in humans and mice show that androgen administration increases myometrial proliferation (Kim et al, ; Lan et al, ; Liu et al, ; Makieva et al, ; Perusquía, Navarrete, Jasso‐Kamel, & Montaño, ; Simitsidellis, Gibson, Cousins, Esnal‐Zufiaurre, & Saunders, ; Xu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, androgen‐induced signaling cascades may have a role in stromal decidualization by regulating matrix metalloproteinases, prolactin, and insulin‐like growth factor‐binding protein 1 (Cloke & Christian, ; Cousins et al, ; Gibson, Simitsidellis, Cousins, Critchley, & Saunders, ; Ishikawa, Harada, Kubota, & Aso, ; Kajihara et al, ). In vivo studies in mice and rats as well as in vitro studies in humans and mice show that androgen administration increases myometrial proliferation (Kim et al, ; Lan et al, ; Liu et al, ; Makieva et al, ; Perusquía, Navarrete, Jasso‐Kamel, & Montaño, ; Simitsidellis, Gibson, Cousins, Esnal‐Zufiaurre, & Saunders, ; Xu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the mice uterus, quantitative in situ hybridization identified uniform labeling of androgen receptor (AR) mRNA in all compartments, including the epithelium [ 10 ]. A recent study described nuclear stromal AR staining in the mouse uterus but was not detected in the luminal or glandular epithelium [ 11 ]. Female global AR knockout mice are sub-fertile [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the uteri of mice, quantitative in situ hybridization detected uniform labeling of Ar mRNA in all compartments, including the epithelium ( 14 ). A recent study reported nuclear stromal AR staining in the mouse uterus but AR was not detected in the luminal or glandular epithelium ( 15 ). A study using a transgenic mouse model of an androgen response element construct fused to a luciferase reporter revealed strong AR activity in the uterus, with the antiandrogen bicalutamide inhibiting luciferase activity ( 16 ).…”
mentioning
confidence: 99%